2021
DOI: 10.3389/fcvm.2021.777016
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Peripheral Arterial Disease: A Narrative Review

Abstract: Peripheral arterial disease (PAD) is a highly prevalent atherosclerotic condition. In patients with PAD, the presence of intermittent claudication leads to a deterioration in quality of life. In addition, even in asymptomatic cases, patients with PAD are at high risk of cardiac or cerebrovascular events. Treatment of PAD is based on lifestyle modifications; regular exercise; smoking cessation; and control of cardiovascular risk factors, including hypercholesterolemia. A growing number of studies have shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 193 publications
0
6
0
Order By: Relevance
“…Finally, due to the multifactorial nature of PAD, using antioxidants as a definitive treatment alone may not be effective [ 6 ]. Therefore, using additional therapies according to the patient’s underlying disease (anticoagulants, antiplatelet agents, antihypertensives, antidiabetic agents, and statins) along with the appropriate amount of antioxidants seems to be more effective [ 6 , 34 ]. Due to the positive feedback between the initiator (cause) of pathogenesis and its consequences, there is an interaction between the oxidative stress level and thrombosis, leading to the elevation of both [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, due to the multifactorial nature of PAD, using antioxidants as a definitive treatment alone may not be effective [ 6 ]. Therefore, using additional therapies according to the patient’s underlying disease (anticoagulants, antiplatelet agents, antihypertensives, antidiabetic agents, and statins) along with the appropriate amount of antioxidants seems to be more effective [ 6 , 34 ]. Due to the positive feedback between the initiator (cause) of pathogenesis and its consequences, there is an interaction between the oxidative stress level and thrombosis, leading to the elevation of both [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statins effectively decrease serum LDL-C and sdLDL-C while increasing HDL-C levels and reduce the susceptibility of apo B of LDL to undergo oxidation and glycation. They also display significant anti-inflammatory properties and improve endothelial function (so-called pleiotropic effects) ( 71 ). Robust evidence supports the fact that use of statins enhances angiogenesis as well as arteriogenesis independent of a cholesterol-lowering mechanism ( 72 , 73 ).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Mondillo et al, reported a 90-m increase in pain-free walking distance in PAD patients after 6 months of simvastatin therapy ( p < 0.005) [ 38 ]. In addition to increasing pain-free walking distance [ 39 ], statins have been shown to increase total walking distance [ 40 , 41 , 42 , 43 , 44 ], reduce severity of IC [ 45 ] and improve overall quality of life [ 43 , 46 , 47 ], especially when combined with an exercise regimen [ 48 ].…”
Section: Role Of Statins In Padmentioning
confidence: 99%